2014
DOI: 10.1016/j.joen.2014.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic and Clinical Outcomes of the Treatment of Immature Permanent Teeth by Revascularization or Apexification: A Pilot Retrospective Cohort Study

Abstract: Introduction This retrospective cohort study compared clinical and radiographic outcomes of endodontic treatment performed in immature non-vital permanent teeth, by apexification (calcium hydroxide or apical barrier with Mineral Trioxide Aggregate (MTA)), versus revascularization. Methods A comprehensive chart review was performed to obtain a cohort of sequential previously completed cases with recalls. Clinical and radiographic data were collected for 31 treated teeth (19 revascularization and 12 apexificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
217
2
10

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
4

Relationship

2
6

Authors

Journals

citations
Cited by 174 publications
(236 citation statements)
references
References 33 publications
7
217
2
10
Order By: Relevance
“…At 12 months, the average within-case percent change from the pre-operative radiograph was 20%. This is comparable to what was observed in other cohort studies including Jeeruphan et al, who reported an average 27% increase with an average of 21 months follow up, and Alobaid et al, who saw a 10% increase with an average of 15 months follow up (4, 18). Differences in within- case radiographic changes could be due to non-standardized radiographs being used in the retrospective cohort studies, which often can reduce the accuracy in measuring the actual radiographic change.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…At 12 months, the average within-case percent change from the pre-operative radiograph was 20%. This is comparable to what was observed in other cohort studies including Jeeruphan et al, who reported an average 27% increase with an average of 21 months follow up, and Alobaid et al, who saw a 10% increase with an average of 15 months follow up (4, 18). Differences in within- case radiographic changes could be due to non-standardized radiographs being used in the retrospective cohort studies, which often can reduce the accuracy in measuring the actual radiographic change.…”
Section: Discussionsupporting
confidence: 90%
“…This was the most robust and consistent radiographic change observed in the population treated in this study. Radiographic evidence of apical closure of revascularized teeth has been observed in other studies at various follow up times (10, 18–20), however, the frequency and time course of the occurrence of apical closure after revasc/revit treatment was not appreciated before this study.…”
Section: Discussionmentioning
confidence: 46%
See 1 more Smart Citation
“…The treatment can result in regression of clinical signs/ symptoms as well as resolution of apical periodontitis. In addition, thickening of the canal walls and/or continued root development may occur in some cases (3)(4)(5). According to the American Association of Endodontists guidelines, the primary goals of RET are resolution of apical periodontitis and elimination of clinical signs/symptoms (6).…”
mentioning
confidence: 99%
“…Immature pulpless teeth are also more vulnerable to injury, losing the ability to sense environmental change and are more prone to root fracture [3, 4]. Traditional treatment of immature teeth is apexification, which involves placing a tri-calcium silicate matrix at the apex [5], or inducing a barrier using calcium hydroxide; however, these techniques are not designed to induce extension of root length or width [6, 7] and generally have poor long-term prognosis [8]. Therefore, strategies to either maintain pulpal health or stimulate the development of new biological tissue are paramount, not only to promote minimally invasive solutions but also to retain or reinstate the capacity of the pulp to generate tertiary dentin and respond to injurious stimuli [9•].…”
Section: Introductionmentioning
confidence: 99%